James - Moore-Keish, Martha L. (Belief: a theological commentary on the Bible, 2019)
Introduction: why James? why now? -- 1:1 "James" greets the "twelve tribes" -- 1:2-8 Faith and wisdom in the midst of trials -- 1:9-11 Poor and rich -- 1:12-15 Enduring temptation -- 1:16-18 Being born of the word -- 1:19-27 Hearing and doing the word -- 2:1-13 Playing favorites -- 2:14-26 Faith without works is dead -- 3:1-12 The dangers of the tongue -- 3:13-18 True and false wisdom -- 4:1-10 Conflict between God and "the world" -- 4:11-12 Do not judge -- 4:13-17 Do not boast about tomorrow -- 5:1-6 Critique of rich oppressors -- 5:7-11 Patience in suffering -- 5:12 On swearing -- 5:13-18 Faithful prayer -- 5:19-20 Bringing home the wanderers.